Pengaruh Pendidikan, Pelatihan, Karier Terhadap Kinerja dan Kompetensi SDI Perbankan Syariah Makassar - Marwal, M. Rafid; Ilham (PT Maju Malaqbi Makkarana, 2024)
This study aims to analyze the effect of education, training, career on the performance and competence of SDI in Makassar Islamic banking, to analyze the influence of SDI competence on employee performance, to analyze the influence of education, training, career through the competence of SDI Islamic Banking Makassar. This study uses a quantitative approach using primary data through a questionnaire to 200 respondents. This research was conducted from July to September 2020. Data were analyzed using the SEM AMOS program. The results showed that: Education has a negative and significant effect on SDI Competence, Training has a positive and significant effect on SDI Competence, Career has a positive and insignificant effect on SDI Competence, Education has a positive and significant effect on Employee Performance. Training has a positive and significant effect on employee performance. Career has a positive and significant effect on employee performance. SDI competence has a positive and significant effect on employee performance, Education has a positive and significant effect on employee performance through SDI competence. Training has a positive and significant effect on employee performance through SDI competence. Training has a positive and significant effect on employee performance